Academic literacy of South African higher education level students: does vocabulary size matter? - Nizonkiza, Déogratias; Van Dyk, Tobie (University of Stellenbosch, 2015)
This study explores the extent to which vocabulary size matters in academic literacy. Participants (first-year students at North-West University) were administered the Vocabulary Levels Test (Schmitt, Schmitt and Clapham 2001). Scores from the test were used to estimate students’ vocabulary size and were subsequently mapped onto the levels distinguished by the Test of Academic Literacy Levels (TALL). Estimates show that, on average, the vocabulary size of first-year students at North-West University is approximately 4,500 word families, a size large enough to allow them to follow lectures in English. Furthermore, students with large vocabularies were found to have higher academic literacy proficiency, which establishes a strong relationship between vocabulary size and academic literacy. This relationship was also observed at the different word frequency bands the Vocabulary Levels Test consists of. These results support previous findings which established a relationship between vocabulary size and reading (cf. Nation 2006), and between vocabulary size and overall language proficiency (cf. Beglar 2010, Meara and Buxton 1987, Meara and Jones 1988, Nation and Beglar 2007), which could be extended to academic literacy. Furthermore, a stronger relationship between vocabulary size and academic literacy was found towards more infrequent word bands, indicating that infrequent word bands may best predict academic literacy. On the basis of these findings, we discuss possible strategies to adopt in order to assist some first-years with expanding their vocabularies.
Keywords: Vocabulary size; academic literacy; academic vocabulary; vocabulary teaching; word frequency